Simulation–Based Comparison of Estimated Methods for the Differencing Fractional Parameter in ARFIMA Model: there is a problem in the abstract. we put another abstract to check the results. - Almahmoudi, Mustafa A.; Khaga, Rida M.; Enaami, Maryouma E. (The Libyan Journal of Science, 2019)
.